Ball game rituals, transculturality and gender in the pre-Hispanic Americas? Questions addressed to the Anthropology of the Americas - Noack, Karoline (2020)
In the longue durée perspective and in an American pan regional dimension, this article intends to analyze the «ball games» which are documented in archaeological and ethnohistorical studies and sources about the Americas, starting in Mesoamerica, throughout the Andean region, up to the lowlands of South America to focus the social continuities and ruptures observed from the «game» as its lens. The physical and socio-political structures as well as the materialities of the «ball games» will be analyzed. An anthropological reading of the sources will be offered. Focusing the continuities and the ruptures in different pre-Spanish, colonial and independent societies of the Americas up to the present, it will be determined, that the «game» cannot be understood only as a game, but as being embedded within a whole continuum of sports, war, and human sacrifice. By this way of analysis, it will be possible to understand the societies of the past better, which were structured, among others, by gender relationships, connecting them to the present.